MANAJEMEN SUPERVISI PENDIDIKAN DALAM MENINGKATKAN KUALTIAS PEMBELAJARAN DI SEKOLAH - Nurmanilda; Akhmad Fawwaz; Nurul Mutmainna; Sulkifli (As-Sulthan Journal of Education, 2026)
Educational supervision management is a crucial aspect in improving the quality of learning processes and outcomes in educational institutions. The background to this research is based on the finding that supervision implementation is still suboptimal, both in terms of planning, implementation, and follow-up, resulting in low learning quality. The purpose of this research is to analyze how educational supervision management can be effectively implemented to improve teacher performance and educational quality. The method used is a qualitative approach with library research, through analysis of various relevant literature sources. The results indicate that effective educational supervision management includes thorough planning, systematic supervision implementation, and continuous evaluation and follow-up. Collaborative and coaching-based supervision can improve teachers' pedagogical and professional competencies. The discussion confirms that the success of educational supervision management is strongly influenced by supervisor competence, effective communication, and support from the educational institution. Therefore, the implementation of structured and sustainable supervision management can be an important strategy in improving educational quality comprehensively.